FEATURES OF TEACHING METHODOLOGY FOR STUDENTS IN ENGLISH AND CHEMISTRY IN THE CONTEXT OF INTERDISCIPLINARY INTEGRATION - Zukhriddin Fakhriddinovich Umirov; Komila Khudoyberdievna Abduvalieva (Журнал естественных наук, 2025)
This article examines the features of teaching methodology for integrating English and chemistry in the context of interdisciplinary education. It explores approaches to combining linguistic and chemical training to develop students’ professional competencies and enhance their motivation for learning. The paper outlines methods and techniques that facilitate the acquisition of English terminology used in chemistry and the development of critical thinking and independent work skills. The importance of using authentic materials, project-based learning, and problem-solving approaches to achieve interdisciplinary interaction is emphasized. Practical examples of implementing the integration of chemistry and English in the educational process are provided